State-of-the-art analysis of the usage and potential of automation in logistics - Helmut Zsifkovits (2020)
© The Editor(s) (if applicable) and The Author(s) 2020. Industry 4.0 technologies enable the automation of information and material flow processes in logistics systems. Automation strategies can be used to increase the efficiency of internal transport, transition, and storage processes, and, moreover, improve service levels and thus strengthen competitiveness. Besides the material flow processes, automation based on state-of-the-art technologies, e.g., cyber-physical system (CPS), Internet of Things (IoT), and physical internet (PI), serves to optimize information flow in logistics processes. This chapter analyzes the importance and potential of effective and efficient logistics operations and outlines enabling technologies for automation in logistics systems. Based on a literature review, the authors discuss both technologies that have already reached market maturity and technologies which have high potential but still require future research and development.